The influence of a stress challenge test on the cognitive performance in a Go/No-Go paradigm and its correlation with HPA system dysregulation in healthy subjects and patients with remitted depression - Lange, C; Krusche, E; Bermpohl, F; Ising, M; Uhr, M; Adli, M (Pharmacopsychiatry, 2009)
Stress tests can be a mean to measure reactivity and activity of the HPA system and can be determined by various parameters. The Trier Social Stress Test provokes stress in a standardized experimental setting and can be used to evaluate the responsevity of the HPA system. Depressed patients show HPA system dysregulation and exaggerated cortisol levels following stress exposure. Increased cortisol levels are associated with impaired performance on various cognitive tasks. When confronted with affective shifting tasks, depressed patients show impairment in shifting their focus of attention and a mood-congruent attentional bias for emotional stimuli. The present study investigated the effects of stress on the performance in an emotional Go/No-Go task in 20 healthy controls and 20 patients with remitted depression. On two testing days an emotional affective shifting task under two conditions was performed: (1) under stress exposure and (2) without stress exposure. Preliminary results of the healthy controls show that stress in combination with higher cognitive demands, such as switching of tasks, negatively influences the performance of the participants. Comparison of healthy controls with the patient population will be presented. Investigating the relation between affective disorders, cognitive performance, stress, variation of HPA system imposes an essential step towards better understanding the association between pathopyhsiological stress patterns and depressive disorders.